2005
DOI: 10.1111/j.1532-5415.2005.53573.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Dependent Differences in Presentation, Risk Factor Profile, and Outcome of Suspected Acute Coronary Syndrome

Abstract: Older patients with suspected ACS were more likely to present atypically and have worse outcomes than their younger counterparts, despite having fewer major risk factors. The results highlight the importance of age as a predictor of adverse outcome and suggest that clinicians need to ensure equitable access to angiography for older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 30 publications
7
20
0
Order By: Relevance
“…Not unexpectedly, dyspnea was associated with a 2.4-fold higher adjusted risk of death and a 2.2-fold higher adjusted risk of death/ AMI compared to typical chest pain. In keeping with these findings, numerous previous studies have provided incremental evidence that patients with atypical symptoms define a high-risk group because they are more likely to be older (26,27 ), female (24,28 ), hypertensive, diabetic, and to have a history of heart failure (24,26 ). The higher risk associated with atypical presentation compared to typical chest pain is substantiated by higher rates of in-hospital heart failure, cardiogenic shock, sustained ventricular tachycardia or ventricular fibrillation, atrial fibrillation or flutter, renal failure, or death (26 ).…”
Section: Discussionsupporting
confidence: 54%
“…Not unexpectedly, dyspnea was associated with a 2.4-fold higher adjusted risk of death and a 2.2-fold higher adjusted risk of death/ AMI compared to typical chest pain. In keeping with these findings, numerous previous studies have provided incremental evidence that patients with atypical symptoms define a high-risk group because they are more likely to be older (26,27 ), female (24,28 ), hypertensive, diabetic, and to have a history of heart failure (24,26 ). The higher risk associated with atypical presentation compared to typical chest pain is substantiated by higher rates of in-hospital heart failure, cardiogenic shock, sustained ventricular tachycardia or ventricular fibrillation, atrial fibrillation or flutter, renal failure, or death (26 ).…”
Section: Discussionsupporting
confidence: 54%
“…Older patients less likely to present with chest pain and more likely present with breathlessness or collapse. 6,7 Group II had significantly higher number of study subjects with smoking habit (p=0.010) than group-I. Conversely group I had significantly higher number of study subjects with hypertension (p=0.024), diabetes mellitus (p=0.001) and dyslipidaemia (p<0.001) than group II.…”
Section: Discussionmentioning
confidence: 84%
“…Our study was supported by Sozia et al, Al-Murayeh et al, Schoenenberger et al, Halon et al, Skolnick and Panduranga et al Sozia et al in their prospective observational study found that older patients with suspected ACS were more likely to have worse outcomes than their younger counterpart despite having fewer major risk factors. 6 Al-Murayeh et al retrospectively reviewed database of 924 Saudi patients with ACS to investigate shortterm outcome of ACS in young population. The results revealed that in hospital one young patient had acute ischaemic stroke and one elderly patient died, 22.4% of the study subjects and 32% of control group were discharged with clinical diagnoses of heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Although therapy appears to be standard [6][7][8][9] only two patients were treated with thrombolytic therapy (TT), and none received coronary reperfusion therapy by percutaneous coronary angioplasty (PCI) perhaps due to the fact that the hospital has no PCI facilities. This circumstance has been previously related to a significantly lesser probability of receiving PCI [10,11]. Moreover a real discrimination against the elderly or ''ageisme'' may be possible.…”
Section: To the Editormentioning
confidence: 89%
“…In conclusion, a specific interdisciplinary program in geriatric cardiology is imperatively required for the treatment of AMI in the very elderly [10], and ageism must be eradicated in clinical practice [11]. …”
Section: To the Editormentioning
confidence: 99%